Increase in prefrontal cortex oxygenation during static muscular endurance performance is modulated by self-regulation strategies. Issue 1 (December 2018) - Wolff, Wanja; Bieleke, Maik; Hirsch, Anna; Wienbruch, Christian; Gollwitzer, Peter; Schüler, Julia
Abstract Enduring physical strain is an important ability and prototypically required in athletic activities. However, little is known about the psychological determinants of endurance performance and their underlying neural mechanisms. Here, we investigated self-regulation as one such factor. We recruited 60 participants who hold intertwined rings for as long as possible while avoiding contacts between them, either with a goal intention or an implementation intention to perform well. Performance was measured in terms of time-to-failure and contact errors. Additionally, we repeatedly assessed ratings of perceived exertion (RPE) and pain (RPP) and used functional near-infrared spectroscopy (fNIRS) to continuously monitor cerebral oxygenation in dorsal and ventral parts of the lateral prefrontal cortex (LPFC), brain regions associated with effortful attentional control and response inhibition, respectively. Performance, RPE and RPP were similar in the goal and the implementation intention condition. LPFC activity increased over time, but its activation level was generally lower in the implementation intention condition. Both effects were particularly pronounced in the dorsal LPFC. Moreover, the balance between effortful and more automatic regulation seems to differ between self-regulation strategies. Our results indicate that self-regulation plays an important role in endurance performance and that self-regulatory processes during endurance performance might be reflected in LPFC activation.